EFFICACY AND SAFETY OF TOCILIZUMAB IN CHILDREN WITH SYSTEMIC JUVENILE ARTHRITIS IN CLINICAL PRACTICE - M. I. Kaleda; I. P. Nikishina (Научно-практическая ревматология)
The paper presents the results of a prospective trial of the efficiency and safety of tocilizumab (TCZ) therapy for sys- temic juvenile arthritis. It analyzes the impact of factors, such as age at onset of the disease, its duration at the time of TCZ therapy initiation,  the number of systemic manifestations, activity of arthritis, and previous experience in using other biological agents, on the efficiency of the therapy. Moreover, the safety of long-term  TCZ usage, reasons for dis- continuation of the therapy, its resumption  possibilities, and ways of enhancing  therapeutic  effectiveness are analyzed.